Solar thermal accumulator with compact plate with phase change material for family dryers - Janampa, Kléber (2021)
In the present work, a solar thermal accumulator has been designed to improve the temporary instability of solar energy in the family drying of products. The structure of the accumulator is defined by thermal simulation in Comsol Multiphysics. The accumulator is modular, with a compact rectangular copper plate whose dimensions are 30 cm x 20 cm x 3 cm that encapsulates 1 kg of paraffin as phase change material. To improve the heat transfer from the phase change material, due to the low thermal conductivity of the paraffin, internal and / or external fins are incorporated into the accumulator to accelerate the process of charging and discharging the thermal energy. When two accumulator units are incorporated in the collector plate of a cabin solar dryer, the temperature of the air entering the drying chamber is stabilized during theaccumulator charging process and when the solar radiation ceases, the accumulated energy allows air to enter the drying chamber with a temperature greater than 30 o C for an interval of 2 h, additional energy that optimizes the product drying process.